The relative persuasiveness of health infographics - Downing Bice, Channing Faith, author; Sivakumar, Gaya, advisor; Castillo, Daniela, committee member; Graham, Daniel, committee member; Long, Marilee, committee member (Colorado State University. Libraries, 2019)
This study explores the persuasiveness of infographics, as a quantitative communication strategy to support medical decision making and health risk appraisal. compared to its equivalent text-based condition, within in the context of promoting STD and STI prevention and screening among young adults. This work uses the ELM as the guiding theoretical framework in a web-based experiment which utilizes a 2 x 1 posttest only experimental design investigates the influence manipulated visual content and message formats have on health-related persuasive message processing among young adults within in the context of promoting STD and STI prevention and screening among young adults. Predictions based on previous literature and empirical testing suggest that enhancing the vividness of the appearance of a health-related message in an infographic format will enhance elaborative processing, resulting in desired health behavior outcomes. To make these predictions, the study poses research questions that explore the cognitive processing and the number of positive thoughts generated by recipients randomly assigned to the infographic condition. In addition to these research questions, this study poses hypotheses that predict elaborative processing, knowledge, and attitude will be greater in the infographic condition, rather than its text-based equivalent, consistent with previous empirical findings. The results of this study can inform further investigations between these pathways and applications to future health communication strategies.